الاقتصاد الأزرق أداة لاستدامة البيئة البحرية الإشارة إلى مبادرة"WESTMED": The blue economy is a tool for the sustainability of the marine environment "reference to the WESTMED initiative" - قعيد لطيفة, (Journal of North African Economies, 2025)
Many countries and international organizations have intentionally launched work plans and initiatives to enhance the utilization of marine resources in order to achieve the desired sustainable development and enhance the provision of decent work opportunities. Among these initiatives that we will address in this study is the sustainable development initiative for the blue economy in the western Mediterranean, where this initiative aims to promote sustainable blue growth and jobs and improve security, safety and environmental conservation and biological diversity in the western Mediterranean, through coordination and cooperation between the countries concerned On the main objectives and a number of priority work areas that will be mentioned later in the context of presenting this initiative.